1984
DOI: 10.1038/311467a0
|View full text |Cite
|
Sign up to set email alerts
|

Protection against the dopaminergic neurotoxicity of 1-methyl-4-phenyl-1,2,5,6-tetrahydropyridine by monoamine oxidase inhibitors

Abstract: 1-Methyl-4-phenyl-1,2,5,6-tetrahydropyridine (MPTP) causes degeneration of the dopaminergic nigrostriatal pathway in several animal species, including humans, monkeys and mice. Changes observed after MPTP administration include marked decrements in the neostriatal content of dopamine and its major metabolites, dihydroxyphenylacetic acid and homovanillic acid, and a greatly diminished capacity of neostriatal synaptosomes to take up 3H-dopamine. In contrast, there is no pronounced loss of serotonin in the neostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
298
0
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 990 publications
(308 citation statements)
references
References 8 publications
7
298
0
3
Order By: Relevance
“…There is growing evidence that mitochondrial damage, particularly to respiratory chain complex I (NADH:ubiquinone oxidoreductase), underlies the pathology of this and other neurological disorders. In rodent model systems, Parkinsonian symptoms have been observed as a result of the inhibition of complex I by the specific inhibitors rotenone (1) and 1-methyl-4-phenyl-1,2,3,4-tetrahydropyridine (MPTP) (2). Moreover, a 30% decrease in complex I activity has been detected in studies on post-mortem brain tissue from PD patients (3), and evidence of complex I subunit depletion has also been reported (4).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…There is growing evidence that mitochondrial damage, particularly to respiratory chain complex I (NADH:ubiquinone oxidoreductase), underlies the pathology of this and other neurological disorders. In rodent model systems, Parkinsonian symptoms have been observed as a result of the inhibition of complex I by the specific inhibitors rotenone (1) and 1-methyl-4-phenyl-1,2,3,4-tetrahydropyridine (MPTP) (2). Moreover, a 30% decrease in complex I activity has been detected in studies on post-mortem brain tissue from PD patients (3), and evidence of complex I subunit depletion has also been reported (4).…”
mentioning
confidence: 89%
“…as an unwanted byproduct of oxidative phosphorylation, when partially reduced electron carriers such as flavins, non-heme iron centers and ubisemiquinone persist long enough to react with molecular oxygen (9,10). Peroxynitrite (ONOO Ϫ ), formed by the reaction of O 2 . with nitric oxide (NO ⅐ ), is implicated as one of the major oxidants responsible for mitochondrial damage (11).…”
mentioning
confidence: 99%
“…This result could be explained by the fact that monoamine oxidase B in the mitochondria converts MPTP to MPP + w h i c h plays an important role for its cytotoxic action (Heikkila et al, 1984) as the ultimate toxic metabolite (Chiba et a l., 1984), and that hydrogen peroxide and hydroxyl radicals are also produced by the interaction of MPP + with mitochondrial NADH dehydrogenase (Adams et al, 1993). However, the PCOOH formation-induced by MPTP was prevented enough to be nondetectable in all groups by G-Rb 1 pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the symptomatic effects observed with selegiline are related to its capacity to inhibit MAO-B, as similar effects are seen with other MAO-B inhibitors (Parkinson Study Group, 1993b, 1994. Similarly, other MAO-B-inhibiting agents can prevent the development of MPTP toxicity (Cohen et al, 1984;Heikkila et al, 1984), suggesting that this mechanism is the basis for the protective effect of selegiline in this paradigm. However, our previous studies (Mytilineou and Cohen, 1985;Mytilineou et al, 1997) and those of several others (Tatton and Greenwood, 1991; Wu et al, 1993) indicate that selegiline protects DA neurons from damage by a mechanism unrelated to the inhibition of MAO activity.…”
Section: Mytilineou Et Almentioning
confidence: 99%
“…As an adjunct to levodopa therapy, selegiline has been shown to provide improved function and reduced motor fluctuations in patients with advanced Parkinson's disease (PD) (Birkmayer and Riederer, 1984;Golbe et al, 1988). Greater interest has centered on selegiline as a putative neuroprotective therapy based on its capacity to block the development of MPTP-induced parkinsonism (Cohen et al, 1984;Heikkila et al, 1984) and oxidative stress secondary to the MAO-B-dependent metabolism of dopamine (Cohen and Spina, 1989;Olanow, 1992). In patients with early untreated PD, controlled clinical trials demonstrated that selegiline delays the emergence of disability necessitating the introduction of levodopa therapy (Tetrud and Langston, 1989; Parkinson Study Group, 1989, l993a) and slows the progression of signs and symptoms (Olanow et al, 1995).…”
mentioning
confidence: 99%